Can hypoxic exercise retard cellular senescence? A narrative review - Tinghuai Huang; Charlotte Tsang; Jianwei Huang (European Review of Aging and Physical Activity)
Abstract Background Senescent cells are defined as normal cells that have undergone irreversible division arrest due to various factors. These cells have been found to play a pivotal role in aging and the development of chronic diseases. Numerous studies demonstrated that physical exercise is effective in anti-aging and anti-chronic diseases. Furthermore, the combination of exercise and hypoxia has been shown to optimize the stimulus of oxygen deprivation and extend cellular lifespan. Objective This narrative review offers an exhaustive analysis of existing literature studying the effect of hypoxic exercise on cellular senescence under various conditions. Methods Four electronic databases underwent title and abstract screening to summarize the effect of hypoxic exercise on cellular senescence under various conditions. Papers were deemed eligible if they examined the effect of hypoxic exercise on cellular senescence in full-text, peer-reviewed journals and published in English. The final search was carried out on May 4, 2024. Studied were excluded if they: (a) did not involve the utilization of hypoxic exercise as a sole intervention or a contributing factor; (b) did not investigate cellular senescence; (c) lacked sufficient information regarding the study design and findings. A total of 2033 articles were obtained from four databases. However, only 11 articles were deemed to meet eligibility criteria after thoroughly examining titles, abstracts, and full-text content. Authorship, publication year, details of the experimental subject, types of exercise, training protocols, organ, tissue or cell, markers of senescent cells examined, and their responses elicited by exercise were diligently recorded. Results This review identified 11 articles for data extraction. The sample sizes varied across a spectrum of complexity, ranging from 4 to 60 (Median=20). The studied population encompassed different healthy cohorts, which comprised sedentary males (n=6), trained males (n=2), mountain climbers (n=1), and older adults (n=2). Included studies preferred using bicycle ergometers (72.7%, n=8) as the exercise modality and 10 studies (90.9%) utilized hypoxia chambers to mimic a normobaric hypoxia environment. Four studies (36.4%) opted to utilize hypoxia chambers to mimic an altitude of 2733 and 4460 m. Additionally, 54.5% of studies (n=6) specifically investigated the effect of hypoxic exercise on lymphocytes, commonly utilizing CD28 (n=3) and CD57 (n=3) as markers of cellular senescence. Four studies (33.3%) examined the impact of hypoxic exercise on erythrocytes using CD47 as the marker for detecting senescent cells. Conclusion These data support the notion that hypoxic exercise can retard cellular senescence of specific cells. In the future, standardization on the type of hypoxic exercise and markers of cellular senescence will be essential. Additionally, greater attention should be given to female populations and patients with different disease states. Lastly, further studies of the optimal form and dosage of exercise and the underlying cellular mechanisms are warranted. Trial registration PROSPERO, identifier CRD42023431601.